Psikoedukasi Keluarga Digital terhadap Kesehatan Mental Keluarga dengan Pasien Gangguan Jiwa - Batmanlussy, Viona Alfonsa; Keliat, Budi Anna; Chandra, Yudi Ariesta (Journal of Telenursing (JOTING), 2024)
This study aims to determine the usefulness of digital family psychoeducation on the mental health of families caring for mentally ill patients. The method used was a systematic review which began with selecting articles using the PIO formulation. The results showed that there was a decrease in burden, depression, anxiety, and family conflict, as well as an increase in quality of life, hope, emotional expression, attitudes, knowledge, and family behavior as caregivers. It is concluded that digital family psychoeducation can be beneficial for the mental health of families caring for mentally ill patients. Keywords: Mental Disorders, Family Mental Health, Digital Family Psychoeducation